Investigating the Relationships between Preservice Teachers' Teacher Readiness, Attitude towards Teaching Profession, and Organizational Attraction through Structural Equation Modeling - Polat, Hakan (Universitepark, 2022)
Background/purpose - The study aimed to investigate relationships between preservice teachers' teacher readiness level, attitudes towards the teaching profession, and organizational attraction perceptions. Materials/methods - Relational survey method, one of the quantitative research methods, was employed in the study. The sample of the study consisted of 341 fourth-grade students at Fırat University's Faculty of Education. The Preparedness to Teach Scale, Attitudes Towards Teaching Profession Scale, and Organizational Attraction Scale were used to collect the study's data. Results - The research revealed a positive and significant relationship between the participants' teacher readiness level, attitudes towards the teaching profession and organizational attraction perceptions. In addition, it was found that the attitude towards the teaching profession had a mediating effect on the relationship between levels teacher readiness and organizational attraction. Conclusion - The study concluded that preservice teachers' teacher readiness level and attitudes towards the teaching profession directly affect their willingness to join educational organizations. Therefore, it is vital for educational organizations that preservice teachers possess higher levels of teacher readiness and sufficiently positive attitudes. © The Author(s) 2022.
Keywords: attitude towards the profession; organizational attraction; preservice teachers; teacher readiness